Sacred Sounds in Transit: The Transformation of Indonesian Ritual Music as a Creative Economy Commodities - Citra Aryandari (ETNOSIA : Jurnal Etnografi Indonesia, 2025)
This critical ethnographic study examines the Indonesian ritual music transformation into creative economy commodities, revealing complex negotiations between cultural preservation and market logic. Its primary contribution is a multi-actor governance model that reveals how Indonesian ritual music is strategically managed within a competitive ecosystem of power.  Through multi-sited fieldwork, this study examines how Indonesian ritual music is reconfigured for tourism, negotiating between spiritual authenticity and commercial viability. Employing a mixed-method approach that combines critical reanalysis of existing ethnographic documentation with targeted primary fieldwork, the study traces power dynamics underlying commodification processes through multi-temporal perspectives. The research engaged a diverse range of informants, including traditional practitioners, PINKAN officials, government representatives, and multi-general artist to ground this analysis. Intensive participant observation during UNESCO recognition processes was supplemented by validation fieldwork across all three sites to capture contemporary transformations. Findings reveal that ritual music's market transit generates stratified outcomes where local communities, state agencies, and global markets compete for definitional authority over cultural meaning. While creative economy initiatives provide economic incentives for cultural transmission, they simultaneously restructure traditional authority, privileging market-oriented aesthetics over cosmological meanings. Traditional leaders function as "ritual CEOs" managing bifurcated musical practices, aristocratic families rebrand ancestral ceremonies as exclusive tourism products, while practitioners navigate UNESCO standardization processes that potentially rigidify living traditions. The research demonstrates that commodification operates through nuanced community strategies maintaining ritual integrity while engaging market opportunities, including "contextual competence" and subversive tactics redirecting revenues toward non-commercial ritual activities. However, technological mediation creates "sonic schizophrenia" where recorded versions exist independently from spatially embedded practices, potentially disconnecting techniques from cosmological foundations. These findings contribute to ethnomusicological understanding by challenging preservation versus commercialization binaries and demonstrating adaptive strategies for cultural sustainability. The study advocates for equitable models centering community agency while preserving cosmological foundations essential to ritual music's cultural vitality.